PKM PELATIHAN MASAYARAKAT DALAM PEMBUATAN SABUN CUCI TANGAN UNTUK MENINGKATKAN PENDAPATAN MASAYARAKAT DESA BATU HULA: PELATIHAN MASAYARAKAT DALAM PEMBUATAN SABUN CUCI TANGAN UNTUK MENINGKATKAN PENDAPATAN MASAYARAKAT DESA BATU HULA - laila, nur - (Jurnal Pengabdian Masyarakat Aufa (JPMA), 2023)
This Community Service aims to increase the community's knowledge about making handsoap and the importance of health through hand washing. Besides that, the specific aim of this community service is to increase the income of the people of Batu Hula Village through training in making handsoap. Through this training, the people of Batu Hula Village are able to independently make handsoap. This Community Service was carried out in Batu Hula Village, Batang Toru District, South Tapanuli Regency, North Sumatra Province. The samples in this service were mothers in Batu Hula Village. The results obtained were that the community was enthusiastic about this training activity and the community was able to make handsoap and the community also hopes that there will be further training that can increase knowledge, especially community income.